Fatigue Characteristics and Numerical Modelling Prosthetic for Chopart Amputation. (16th November 2020) - Abbas, Saif M.; Kubba, Ammar I.
Abstract : This research is looking for three laminated composite material groups. These three groups were utilized in experimental investigation to find their mechanical properties. These properties have been used to design and manufacture a socket for a partial foot prosthesis using an ANSYS model. This socket was manufactured with a vacuum pressure device to improve its properties. The socket composite material was tested for tensile and fatigue properties; then, its results were used in the ANSYS model. The composite material matrix was laminated in an 80 : 20 ratio, and there were three types of reinforcement lamination material (Perlon, glass fiber, and carbon fiber). The mechanical property results of these tests were found as follows: using only-Perlon reinforcement, the properties are σ y = 33.6 MPa, σ ult = 35.6 MPa, and modulus of elasticity = 1.03 GPa ; using (3Perlon +2carbon fiber +3perlon) layers, the properties were σ y = 65.5 MPa, σ ult = 92.5 MPa, and modulus of elasticity = 1.99 GPa ; and using (3Perlon + 2 glass fiber + 3perlon) layers, the results were σ y = 40 MPa, σ ult = 46.6 MPa, and modulus of elasticity = 1.4 GPa . The ANSYS model used the boundary condition from the measured contact pressure between the socket and the patient's stump. The MatScan (F-socket) pressure sensor utilized these interface pressure measurements. The maximum values for the pressure were found as follows: 190 kPa and 164 kPa, which are recorded in the posterior and lateral locations, respectively. The calculated factor of safety for the prosthesis that has been made from a selected composite material with the following layers (3 Perlon+2 carbon fiber+3 Perlon) is 1.037 which is safe for design prosthetic applications. From this study, more prosthetic designs can be modelled and manufactured using this approach. Prosthetics and orthotics are usually custom-made for each patient according to its specific requirements. So, it will be very helpful to find a procedure to analyze the prosthetics before manufacturing it.